The interpretative nature of teachers' assessment of students' mathematics: Issues for equity - Morgan, C; Watson, A (2002)
This paper discusses fairness and equity in assessment of mathematics. The increased importance of teachers' interpretative judgments of students' performance in highstakes assessments and in the classroom has prompted this exploration. Following a substantial theoretical overview of the field, the issues are illustrated by two studies that took place in the context of a reformed mathematics curriculum in England. One study is of teachers' informal classroom assessment practices; the other is of their interpretation and evaluation of students' formal written mathematical texts (i.e., responses to mathematics problems). Results from both studies found that broadly similar work could be interpreted differently by different teachers. The formation of teachers' views of students and evaluation of their mathematical attainments appeared to be influenced by surface features of students' work and behavior and by individual teachers' prior expectations. We discuss and critique some approaches to improving the quality and equity of teachers' assessment.